PENGARUH MODEL PEMBELAJARAN KOOPERATIF LEARNING TEKNIK TERHADAP TERHADAP KETERAMPILAN PESERTA DIDIK DI PONDOK PESANTREN PUTRI AZZAHRO PALEMBANG - Lisa Ayu Tiasti; Karoma Karoma; Mardeli Mardeli (PAI RAFAH, 2021)
Education has an important role in improving the quality of a nation, quality education will create a quality generation as well. This century requires students to have the skills to be ready to face existing challenges. Education is directed at preparing students who have skills, especially the ability to think critical thinking or critical thinking. This study aims to determine the effect of implementing cooperative learning model lerning, greeting techniques and questions on critical thinking skills. This research uses quantitative research, with samples using saturated sampling techniques. The data obtained in this study were obtained from the results of a questionnaire (questionnaire) and documentation. Further analyzed with the collected data then recapitulated after the data was collected from various sources, then the data were analyzed using quantitative data analysis techniques.After analyzing the effect of the application of the cooperative learning model learning the technique of sending greetings and questions on the skills of students at the Pondok Pesentren Putri Azzahro Palembang using the product moment correlation formula, it can be stated that there is a significant effect between the two variables, namely the application of the cooperative learning model, the technique of sending greetings and questions and Skills. This is indicated by ttable = 2.23 and tcount = 2.36, then tcount> ttable. Then the coefficient of determination / destermination is 12%. This shows the effect of the application of the Cooperative Learning Technique Learning Model on the Skills of Students at Pondok Pesentren Putri Azzahro Palembang. While the remaining 88% critical thinking skills at Pondok Pesentren Putri Azzahro Palembang are influenced by other factors.